2017
DOI: 10.1002/cpt.753
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Renaissance of Glucocorticoids in Rheumatoid Arthritis?

Abstract: The first therapeutic use of glucocorticoids was in a patient with severe rheumatoid arthritis and the symptomatic benefit was astounding. Adverse effects from increasingly large doses led to them being overshadowed, dismissed as inappropriate treatment, and ignored for 20 years - but in the last 2 decades, the accumulating evidence and clinical practice suggest there is a justified renaissance in their use as a first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…However, there is no consensus on the optimal duration of treatment with glucocorticoids due to varying findings of the degree of adverse effects. [34] Combination therapy with GCs and DMARDs has led to quick remission, substantial delay in disease progression, and excellent protection against cartilage and bone erosion. [35] The clinical importance of glucocorticoids in treating RA must be clarified, considering that a few studies on the administration of GCs alone reported excellent alleviation of RA but failed to provide con-vincing evidence, respectively.…”
Section: Tsdmards Jak Inhibitormentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is no consensus on the optimal duration of treatment with glucocorticoids due to varying findings of the degree of adverse effects. [34] Combination therapy with GCs and DMARDs has led to quick remission, substantial delay in disease progression, and excellent protection against cartilage and bone erosion. [35] The clinical importance of glucocorticoids in treating RA must be clarified, considering that a few studies on the administration of GCs alone reported excellent alleviation of RA but failed to provide con-vincing evidence, respectively.…”
Section: Tsdmards Jak Inhibitormentioning
confidence: 99%
“…[35] The clinical importance of glucocorticoids in treating RA must be clarified, considering that a few studies on the administration of GCs alone reported excellent alleviation of RA but failed to provide con-vincing evidence, respectively. [34,35] In addition, several adverse effects of higher glucocorticoid dosages have been reported, including bone loss and high-risk fractures. Patients with glucocorticoids at low doses over the long term have also exhibited other adverse effects, such as susceptibility to infection, alterations in glucose metabolism, cutaneous atrophy, cataract formation, and proximal myopathy.…”
Section: Tsdmards Jak Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroids (CS) are a class of pleiotropic immunosuppressive agents used in the treatment of various inflammatory and autoimmune diseases, such as asthma (Barnes, 1998) and rheumatoid arthritis (Kirwan and Gunasekera, 2017). Their potent immunosuppressive properties also form the basis for their use in preventing rejection of solid organ transplants (Taylor et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, glucocorticoids showed stunning effects, but it rapidly became clear that an uncritical use causes severe long‐term adverse events, best documented for the iatrogenic Cushing syndrome. In their interesting Opinion article, Kirwan and Gunasekera question if there is “a renaissance of glucocorticoids in rheumatoid arthritis?” They conclude that combined therapy using conventional disease‐modifying antirheumatic drugs (cDMARD) such as methotrexate together with low‐dose glucocorticoids could be the “new gold standard” for early RA treatment. Considering that, on the one hand, current evidence‐based guidelines recommend that patients must fail cDMARD before applying biologic DMARD in RA management, and, on the other hand, there is strong evidence of the success of biologics in patients with moderate to severe RA, this question needs to be carefully discussed.…”
mentioning
confidence: 99%